2019
DOI: 10.3389/fpsyg.2019.02280
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Self-Esteem in Combat and Team Sports

Abstract: The aim of this research was to examine whether psychological variables which make up basic dimensions of personality and self-esteem distinguish competitors in combat sports from competitors in team sports. The research included 149 respondents, aged 19 to 27 years. The Self-Esteem Scale questionnaire was used to measure self-esteem. The BFI inventory was used to measure personality traits according to the Big Five model: Extraversion, Neuroticism, Conscientiousness, Agreeableness, and Openness to Experience.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 37 publications
(55 reference statements)
3
30
0
Order By: Relevance
“…However, social learning theory principles cannot explain the absence of the higher off- problems such as aggression (Donnellan et al, 2005). Bojanić et al (2019) showed higher self-esteem of team sports athletes in comparison to combat sports athletes.…”
Section: Discussionmentioning
confidence: 92%
“…However, social learning theory principles cannot explain the absence of the higher off- problems such as aggression (Donnellan et al, 2005). Bojanić et al (2019) showed higher self-esteem of team sports athletes in comparison to combat sports athletes.…”
Section: Discussionmentioning
confidence: 92%
“…The moderation effect of financial awards was detected as significant between the subscale confidence and achievement motivation and cognitive trait anxiety. Confidence is made up of self-assessment of one's own activities, the outcome of the social comparison process with others, and a reflection of fan, audience, or media support (Keegan et al, 2010;Harwood et al, 2015;Kaplánová and Gregor, 2018;Bojanić et al, 2019). If the environment is favorable and supportive, it is manifested by increasing confidence and the motivation to achieve success of athletes; if the environment is hostile, it reduces the performance (Hays et al, 2009;Kaplánová, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…The study of anxiety during volleyball and basketball competitions showed a statistically nonexistent lower level of the variable (by 9%) in basketball players [3]. Comparisons between the group of martial arts (wrestling, karate, judo, kick boxing, taekwondo and MMA) and the group of team games (football, basketball, volleyball and handball) showed significantly higher levels of self-esteem and neuroticism of game players [4].…”
Section: Introductionmentioning
confidence: 87%